Selling Sex as an Edgework: Risk Taking and Thrills in China's Commercial Sex Industry - Tsang, Eileen Yuk-Ha (International journal of offender therapy and comparative criminology, 2019)
Academic discussions of the sex industry need to consider sex worker's experience within the conceptual framework of "edgework." Edgework is voluntary risky activity that combines danger with excitement and emotional pleasure. This article argues female sex worker must weigh possible outcomes in terms of the resulting benefits or consequences. The notion of edgework articulated by Stephen Lyng proposed there is a fine line for risky behavior going from pleasurable and manageable to turning dangerous and chaotic. This description of edgework applies to female sex workers, and needs to be extended to individualization in the Chinese context. Research data collected from two distinct ethnographies in Dongguan (195 sex workers) and Hong Kong (39 sex workers). The research findings provide insights into the experiences and motivations of an underexamined niche segment of sex workers. A significant number of sex workers embody the perspective of edgework to maintain self-esteem in difficult circumstances. For example, edgework explains several aspects of sex work including notions of excitement and personal pleasure, developing skills within the craft, developing interpersonal networks with peers, and gaining personal happiness through fulfilling sexual desire.